AN ANALYSIS OF FIGURATIVE LANGUAGES USED IN SIMPLE PLAN'S SONG LYRICS IN THE ALBUM ENTITLED "GET YOUR HEART ON!" - ., Ni Made Yudi Harsini; ., Prof. Dr.I Ketut Seken,MA; ., Dewa Ayu Eka Agustini, S.Pd., M.S. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujuan untuk menemukan macam-macam majas yang digunakan dalam lirik lagu Simple Plan dan makna yang tersirat berdasarkan penggunaan majas dalam lirik-lirik lagu tersebut. Untuk mengaplikasikan penelitian ini, 13 lagu dalam album Simple Plan yang berjudul â€œGet Your Heart On!â€ telah dipilih untuk dianalisis menggunakan teori oleh Laurence Perrine (1982). Rancangan penelitian deskriptif dengan pendekatan kualitatif diimplementasikan dalam penelitian ini. Penelitian ini menunjukkan bahwa: (1) terdapat sembilan macam majas yang dipergunakan dalam lirik-lirik lagu Simple Plan dalam album mereka yang berjudul â€œGet Your Heart On!â€, yaitu: Metaphor, Simile, Personification, Overstatement/ Hyperbole, Understatement, Metonymy, Paradox, Symbol dan Verbal Irony; (2) makna yang tersirat dalam penggunaan majas dalam lirik-lirik tersebut sebagian besar berkaitan dengan makna konotatif.Kata Kunci : Majas, Lirik-lirik Lagu, Makna Tersirat. This study aimed to find out the kinds of figurative language used in Simple Planâ€™s song lyrics and the meaning implied based on the use of figurative language in those lyrics. To administer this study, 13 songs in Simple Planâ€™s album entitled â€œGet Your Heart On!â€ were selected to be analyzed by using Laurence Perrineâ€™s theory (1982). Descriptive design within qualitative approach was implemented in this study. This study reveals: (1) there are nine kinds of figurative language are used in Simple Planâ€™s song lyrics in their album entitled â€œGet Your Heart On!â€, such as: Metaphor, Simile, Personification, Overstatement/ Hyperbole, Understatement, Metonymy, Paradox, Symbol, and Verbal Irony; (2) the meaning implied based on the use of figurative language in those lyrics mostly deal with connotative meaning.keyword : Figurative Language, Song Lyrics, Meaning Implied.